Institutional Design In Collaboration To Strengthen Food Fortification In Consumption Salt Smes In Pati Regency - Rina Nuryanti; Hermin Indah Wahyuni; Roso Witjaksono (Jurnal Indonesia Sosial Teknologi, 2024)
Fortifying salt with iodine is one of the government's strategies to achieve food and nutritional security. Iodine deficiency can hinder mental and intelligence development, affecting the quality of Human Resources. Pati Regency can contribute to strengthening food fortification with the potential of its salt-consumption SMEs. However, the test results stated that 40.70% of the salt consumption of SMEs in Pati needed to meet standards. The fortification program is implemented and integrated into the government and private sectors. Successful fulfillment of product quality by SMEs requires effective collaboration between development institutions and business actors and good coordination between the development institutions. Institutional design contributes to the collaboration process that occurs. This research aims to analyze the institutional design and problems in collaboration with development actors to develop consumer salt SMEs in the Pati Regency. The research uses qualitative methods, collecting data through observation, in-depth interviews, document studies, and FGDs. The development of consumer salt SMEs in Pati Regency involves government institutions at the district level, namely the Ministry of Trade and Industry and Bappeda, at the provincial level, namely the Ministry of Industry and Trade and BBPOM in Semarang, as well as non-government organizations, namely the NGOs Nutrition International Indonesia and APROGAKOB. Institutional design in collaboration with actors developing iodized salt SMEs requires strengthening the dimensions of basic rules, participation, exclusive forums, and transparency. Strengthening the institutional dimension will increase collaboration so that the potential of Pati Regency can support strengthening the fortification of salt consumption